Synchronverter-based STATCOM control with voltage imbalance compensation - Gomes, Lucas do Nascimento (2020)
In this work, a synchronverter-based control strategy is proposed to operate the STATCOM as a synchronous compensator. Moreover, to cope with unbalanced conditions that may appear at the grid, a novel voltage imbalance compensation control is developed to work harmoniously with the main synchronverter model. The used base synchronous generator model is derived from a general AC machine in space vector representation. Practical details about the controller design are addressed as well as a small-signal model for stability analysis and parameter tuning. Two scenarios are simulated: large-scale and small-scale system, the latter being used as a validation step for implementation in a small experimental setup. Both simulations and experimental results confirm the suitable performance of the proposed control.